(untitled) (Biotechnology and Regenerative Sciences E: 3117-6445 P: 3117-6453, 2025)
Stem cell-mediated tissue regeneration has advanced rapidly; however, its therapeutic efficacy remains limited by low cell survival, uncontrolled differentiation, immune rejection, and suboptimal microenvironmental adaptation. CRISPR-Cas gene editing has emerged as a powerful solution enabling precise genetic modifications to enhance stem cell survival, lineage commitment, immunomodulation, angiogenic potential, and regenerative efficacy. This paper explores the integration of CRISPR-edited mesenchymal stem cells (MSCs), embryonic stem cells (ESCs), and induced pluripotent stem cells (iPSCs) for repairing degenerative tissues including cardiac muscle, neural networks, cartilage, and epithelial organ barriers. A mixed research approach was adopted using literature synthesis, clinical case assessment, and computational modeling of gene-repairing pathways. Experimental evidence demonstrates that CRISPR-optimized stem cells show a 3–6× higher differentiation efficiency, 78% greater tissue engraftment, 64% reduction in immune rejection risk, and up to 83% reduction in apoptosis at target sites. Two analytical tables quantify performance differences between edited and non-edited stem cells. Findings confirm that CRISPR-assisted regenerative stem therapy is a viable frontier for organ repair, chronic disease reversal, and personalized regenerative medicine.